Enrichment of white flour with spices positively impacts safety and consumer acceptance of bread. (25th October 2020) - Issaoui, Manel; Nesrine, Mahfoudhi; Flamini, Guido; Delgado, Amélia
Summary: Aiming at increasing the nutritional value and sensory quality of bread, we assessed the enrichment of white flour with different levels of powdered cinnamon and pomegranate peel, through rheological, nutritional, aromatic, textural and sensory analyses. These extra ingredients were chosen for their richness in bioactive compounds, and they differently affected bread quality. In relation to raw flour, introduced ingredients slightly decreased moisture and protein content, while increasing ash, fibre and radical scavenging activity, which can be attributed to the sharing of aromatic compounds by cinnamon and pomegranate peel during the bread making process. When cinnamon was incorporated at 1%, the content of all furan derivatives was reduced up to 1/4 of initial value, 2‐pentyl furan totally disappeared, and furfuryl alcohol was reduced to 2.1%. Despite enriched bread's texture was slightly worse, it was still acceptable in sensory tests, as 150 interviewed naive consumers preferred the new product over the control. Abstract : Cinnamon and pomegranate peel powder were incorporated into white wheat flour, enhancing the nutritional value of resulting bread, while meeting consumer's preferences for taste and texture.